Behavioral structure and demography of subarctic Clethrionomys gapperi and Peromyscus maniculatus - Mihok, Steve (Canadian Journal of Zoology, 1979)
A subarctic rodent community of Clethrionomys gapperi and Peromyscus maniculatus was censused with multiple-capture traps in contrasting years of population growth. Clethrionomys gapperi was involved in few multiple captures and was caught in small groups. Repeat multiple captures of the same individuals were rare. Mature females were territorial and were mainly caught with mature males. Mature males had large, extensively overlapping ranges and were mainly caught with mature voles. Immatures had small, moderately exclusive ranges and were involved in more multiple captures than were mature voles. Patterns of association in C. gapperi were random.Peromyscus maniculatus was involved in numerous multiple captures and was occasionally captured in large groups. Individuals were often repeatedly captured with the same individuals. Except for mature males, most animals had extensively overlapping ranges. The basic social unit consisted of a mature male, a few mature females, and a number of young. Numerical changes were principally related to variation in juvenile survival and winter mortality. The pattern of multiple captures did not vary over a wide range of conditions. Variation in the frequency of multiple captures was indicative of spatial organization and social structure, and was not related to demographic changes.